ʼBrug gi mi rig pa can Padmaʼi-tshe-dbaṅ-bkra-śis daṅ Sun-dar Bkra-śis gñis kyi blo bsral, 1900 (Druk Sherig Press, 1978)
Two anonymous folk ballads in the blo-bsral form recounting the exploits of two Bhutanese heroes of the 19th century.